“Eu sou andina!”: as faces e contrafaces da mulher boliviana na Praça/Feira da Kantuta - Misaka, André Katsuyoshi (2020)
The process of building knowledge for this research is also the choice of a road of commitment and visualization of human existences that permeate occupied spaces in the city of São Paulo. Thus, listening to human existences with simplicity, attention and a sharp eye provides assimilation of the sense of voice and speech and to the meanings that these factors point to. So, due to make academic experiences the compass to feel the soil of this city, full of nationalities, the research trajectory presents a deep search for knowledge, focusing on visualizing the life processes of the wonderful women who collaborated and still collaborate with their apprehensions of world, and, in this academic outline, the Andean and Bolivian woman who occupy Kantuta's Sao Paulo territory. To link this procedural compound, the researcher, then an oralist, listens with colors that humanize the worldview, through the speeches, comments and experiences of the people who live in “one of the many Sao Paulos inside Sao Paulo”, that is, the people who live in the same municipality under so different conditions. Besides, the researcher seeks to unite occupied territory and the presence of women, especially the Andean woman who uses the Kantuta Square and Kantuta Fair, in Pari, a neighborhood in Sao Paulo, as a space for sociability and expression of her culture and coexistence. She was the color that came to give academic meaning, and there was no other possibility but Marxist historicaldialectical materialism for interpretation and for writing. The territory is around the Kantuta Square, where Kantuta Fair brightens up this urban space every Sunday, and the methodology of Oral History made the power of the word fly over the academic eye! Kantuta Square and Kantuta Fair are changed with the presence of Bolivians who access and occupy this space/territory for the exercise of culture, from opaque spaces during the week to lively ones on Sundays, connecting the diversity of human manifestations that interact with the urban to the diversity of faces and shapes. The theoretical framework guided the empirical research carried out with a marketer/trader at Kantuta Fair to understand the centrality and the meaning that this territory has in her life. Methodologically, Oral History collaborated in the process of revealing reality, and the understanding of Andean sociability in Kantuta Square came up with the powerful analysis of this Andean woman's narrative. Some elements will be the path for the academic reflections and the corresponding reading will demonstrate the researched territory, the lived, experienced and built space, and the wanderings through the territory made it possible to find out the geographical spaces. The discussion of Andean sociability, in the Sao Paulo context, emphasizes the cosmopolitan atmosphere, so present in Sao Paulo, as well as the occupation of its territory. The existential support of Mamita, the research participant, with her orality, highlighted the intrinsic relationship between being a woman and being Andean, with a special focus on sociability, protection networks and culture as resistance. In this part of the analysis, Mamita's speeches showed what the landscape was like, and its reading will bring the reader the delight of the everyday universe